17.6% Conversion Efficiency Multicrystalline Silicon Solar Cells Using the Reactive Ion Etching with the Damage Removal Etching. (6th March 2012) - Shim, Ji-Myung; Lee, Hyun-Woo; Cho, Kyeong-Yeon; Seo, Jae-Keun; Kim, Ji-Soo; Lee, Eun-Joo; Choi, Jun-Young; Oh, Dong-Joon; Shin, Jeong-Eun; Kim, Ji-Sun; Kong, Ji-Hyun; Lee, Soo-Hong; et al.
Abstract : For lower reflectance, we applied a maskless plasma texturing technique using reactive ion etching (RIE) on acidic-textured multicrystalline silicon (mc-Si) wafer. RIE texturing had a deep and narrow textured surface and showed excellent low reflectance. Due to plasma-induced damage, unless the RIE-textured surfaces have the proper damage removal etching (DRE), they have a drop in V oc and FF. RIE texturing with a proper DRE had sufficiently higher short circuit current ( I s c ) than acidic-textured samples without a drop in open circuit voltage ( V oc ) . And in order to improve efficiency of mc-Si solar cell, we applied RIE texturing with optimized DRE condition to selective emitter structure. In comparison with the acidic-textured solar cells, RIE-textured solar cells have above 200 mA absolute gain in Isc. And optimized RIE samples with a DRE by HNO3 /HF mixture showed 17.6% conversion efficiency, which were made using an industrial screen printing process with selective emitter structure.